Cover Plants-Mediated Suppression of Fusarium Wilt and Root-Knot Incidence of Cucumber is Associated With the Changes of Rhizosphere Fungal Microbiome Structure-Under Plastic Shed System of North China - Ali, Ahmad; Elrys, Ahmed S.; Liu, Liangliang; Iqbal, Muhammad; Zhao, Jun; Huang, Xinqi; Cai, Zucong (Frontiers in Microbiology, 2022)
Cover crops are known to alleviate the adverse effects of continuous cropping by influencing plant health and changing host fungal-microbiome structures. However, insight into the shift of rhizomicrobiota composition and their effects on plant growth performance and resistance mechanism is still limited under plastic shed cultivation (PSC). Four leafy vegetable rotations namely spinach rotation (SR), non-heading Chinese cabbage rotation (NCCR), coriander rotation (CR), and leafy lettuce rotation (LLR) were used as cover crops in 7-years of continuous cucumber planted soil (CC). Their ecological impacts were studied for plant growth performance, replant diseases incidence rate, and rhizosphere fungal microbiome. Compared to CC, SR showed a highly suppressive effect on fusarium wilt, i.e., by 13.2% in the spring season, while NCCR decreased the root-knot nematode incidence rate by 8.9% in the autumn season. Such protective effects caused a significant increase of shoot and fruit biomass and thus sustained the fruit quality of cucumber. High-throughput sequencing revealed that the CR, SR, and NCCR treatments altered the fungal community composition by increasing the abundance of the beneficial fungal genera, decreasing pathogenic taxa, and fostering the saprotrophic and symbiotic functions. However, the relative abundance of most of the potentially pathogenic fungal genera increased in CC and LLR cropping. There were 8 potential pathogens and 10 beneficial or biocontrol fungi characterized. It was found that Paecilomyces, Chaetomium, Cladorrhinum, Zopfiella, Purpureocillium, and Metarhizium were the putative biocontrol microbes that positively affected plant growth and replanted diseases inhibition. The characterized Fusarium, Dactylonectria, Alternaria, Gibberella, and Aspergillus were the key pathogenic fungal agents found to be negatively associated with plant growth characters, suggesting that rhizomicrobiome may play an important role in the occurrence of disease incidence of cucumber plants. Considering the ecological potential of some cover plants, this study suggested that rotation with spinach, non-heading Chinese cabbage, or coriander can enhance rhizosphere immunity by triggering the development of plant-protective fungal microbiomes under plastic shed cucumber cultivation.